Ocular prosthesis using external plate technique - D Kalpana; Smitha Sharan; Joel Koshy Joseph; Sampath Kumara Raju Kurapati; Nadira Jabeen; Iti Badola (Wolters Kluwer Medknow Publications, 2018)
This case report describes fabrication of eye prosthesis for an unfortunate individual, using external plate technique. The treatment commenced with personal psychological counseling and reassuring him about the outcome after the treatment. Clinically, because of reduced eyelid opening and intraocular space, conventional small-sized conformers did not fit, and hence, impression was made with custom-made external plate technique. The outcome of the treatment was found satisfactory and was well accepted by the patient.